2023
DOI: 10.1111/aogs.14506
|View full text |Cite
|
Sign up to set email alerts
|

The acceptability of implementing patient‐reported measures in routine maternity care: A systematic review

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
(669 reference statements)
0
3
0
Order By: Relevance
“…One barrier to adaptation of PROMs in routine use is patient burden. In the field of maternity care, a systematic review by Chen et al ( 36 ) found that one factor hindering the acceptability of PROM collection was that the patients were concerned about the length of the questionnaires and the inadequacy of instructions. They offered suggestions for increasing response rate, such as explaining the purpose of the questionnaires to the patients and giving clear instructions, which could be applicable in the elderly population as well.…”
Section: Discussionmentioning
confidence: 99%
“…One barrier to adaptation of PROMs in routine use is patient burden. In the field of maternity care, a systematic review by Chen et al ( 36 ) found that one factor hindering the acceptability of PROM collection was that the patients were concerned about the length of the questionnaires and the inadequacy of instructions. They offered suggestions for increasing response rate, such as explaining the purpose of the questionnaires to the patients and giving clear instructions, which could be applicable in the elderly population as well.…”
Section: Discussionmentioning
confidence: 99%
“…The focus of both measures is centered on the paradigm of personcentered care [11], prioritizing capturing the experiences and outcomes that matter to individuals over clinical outcome measures [12,13]. Similar to other healthcare specialties, interest in PROMs and PREMs has grown in maternity, pregnancy, and childbirth care [14]. From this contextualization, maternal satisfaction related to their breastfeeding process, directly linked to PROMs, should also be included as an appropriate outcome indicator.…”
Section: Introductionmentioning
confidence: 99%
“…The TFA defines acceptability as a multifaceted construct, comprising of seven domains (affective attitude, burden, ethicality, intervention coherence, opportunity costs, perceived effectiveness, and self-efficacy, see Table 1 for construct definitions) that can be applied at different timepoints (before, during or after an intervention) to assess the prospective, concurrent, or retrospective acceptability of an intervention. Perinatal research has used the TFA to assess acceptability in a variety of healthcare contexts (e.g., 57 61 ), including the use of exposure therapy among pregnant women with elevated anxiety ( 62 ), and a systematic review on the acceptability of implementing patient reported measures in routine maternity care ( 63 ). However, the authors know of no research that has used the TFA to assess the acceptability of suicide-related screening items to perinatal women.…”
Section: Introductionmentioning
confidence: 99%